ASSA13-01-6 Association of C-Reactive Protein Gene T-757C Polymorphism in the Promoter Region with Unstable Angina Pectoris - He, Guoping; Meng, Qi (Heart (British Cardiac Society), 2013)
ObjectiveTo investigate the impossible association between C-reactive protein (CRP) gene T-757C polymorphism in the promoter region and unstable angina pectoris (UAP) in a Chinese Han population of Suwan region. Methods This study was conducted with a case-control design including 165 patients with UAP (UAP group) and 282 control subjects who were free from coronary artery disease through coherence checks (control group). The T-757C polymorphism in CRP gene was determined by polymerase chain reaction and restriction fragment length polymorphism analysis. Results Compared with the control group, the frequencies of TT, TC and CC genotype were not significantly different in UAP group (P > 0.05). The prevalence of T allele was 77.6% and 79.1% (P > 0.05), respectively in the UAP group and control group. Multivariate logistic regression analysis indicates that there was no significant correlation between CRP gene T-757C polymorphism and UAP (P > 0.05). Conclusions Our findings suggest that the T-757C polymorphism in CRP gene may be not the risk for UAP among the Chinese Han population of Suwan region.